O projeto 'Edição Digital dos Vocabulários da Academia das Ciências': o VOLP-1940 - Salgado, Ana; Costa, Rute (Revista da Associação Portuguesa de Linguística, 2020)
This paper presents the Digital Edition of the Vocabularies of the Academy of Sciences project, which aims to digitise the spelling vocabularies of the Lisbon Academy of Sciences (ACL) in order to create a digital lexicographic corpus bringing together the printed versions of all these lexicographical reference works – the 1940, 1947, 1970, and finally the 2012 editions. The first stage started with the Vocabulário Ortográfico da Língua Portuguesa [Orthographic Vocabulary of the Portuguese Language] (VOLP-1940), our case study. After digitising this vocabulary, the work described here focuses on the linguistic annotation of VOLP-1940 using eXtensible Markup Language (XML), an annotation metalanguage, and following the annotation directives of the Text Encoding Initiative (TEI), more specifically the application of TEI Lex-0, a new TEI sub-format. We aim to highlight the need for rigorous linguistic data processing in the creation of new lexical resources to increase the quality of their description and applicability.